Bridges between people: nonverbal mediation in an intercultural perspective and training proposals - Mignosi, Elena (Studi sulla Formazione/Open Journal of Education, 2019)
Starting from the meaning of  terms prejudices and mediation, the paper will deal with the theme of “intercultural mediation”, discussing aspects that characterize it, focusing on the non-verbal and creative elements.  It will than reflect upon the necessary professional skills and on possible trainings through the body-artistic language (focusing on dance-movement therapy methodology), drawing inspiration from training experiences with professionals who face emergency situations within very complex social contexts. Italy receives 89% of the unaccompanied foreign minors arriving in Europe. However, Italy does not have adequate laws in place to initiate life projects and social inclusion which could help the overwhelming influx of refugees and migrants. In this very complex situation non-verbal competences can give the possibility to build  bridges between people and to create social networks, that could help bring about more effective actions and, may be, political change